Effect of training after discharge on re-admission and re-hospitalization of patients with heart failure (randomized single-blind clinical trial) - Pazhuheian, Forough; Abadi, Alireza; Zayeri, Farid; Baghfalaki, Taban; Amini, Payam; Laal, Nastaran; Ahmadi, Parisa; Pazhuheian, Farhad (Archives of Advances in Biosciences, 2018)
Discharge is the process of transferring a patient from hospital which involves a transfer of responsibility from inpatient service providers or hospitalist to the patient and primary care physicians. Inappropriate follow up after discharge will increase the risk of re-admission and re-hospitalization which leads to the poor performance of the health system. The aim of this study was to determine the effect of physician's caring after discharge on re-admission and referral to doctors.This study was conducted as a clinical trial on patients with early intervention for educational instruction. The clinical trial was conducted at a later stage on 120 patients with heart failure who were hospitalized in Taleghani Hospital, Tehran. For a period of five months after discharge, using block randomization, the subjects were divided into two groups, including intervention and control groups. At the time of discharge, the patients in the intervention group received instructions and were trained by physicians, while no intervention was applied for the subjects in the control group. In addition to demographic questions, the patients were asked about two main outcomes, i.e. "re-admission" and "referral to doctors". To collect the required data, the subjects in both groups were contacted via telephone calls (nine times) every week in the first month after discharge and two times per week in the following two months. Generalized linear mixed effects model method was used for evaluating the effect of physicians caring after discharge on re-admission and re-hospitalization.The results of this study showed that with the passage of time (weekly) after discharge, there was a significant increase in the rate of re-admission in the control group, while there was no significant increase in re-hospitalization. There was no statistical evidence showing a significant difference between the rates of re-admission along with the time in the treatment intervals. In other words, the patients in the control group experienced a significant increase in the odds ratio of re-admission over the time.